Kecerdasan Manusia dan Hubungannya dengan Wahyu: Analisis Tentang Potensi Panca Indera, Intelligence Quotient, Emotional Quotient, Spiritual Quotient, Irfani, dan Ma’rifah - Ashar, Maria Ulfah; Aderus, Andi; Satalia, Indo (Aqidah-Ta: Jurnal Ilmu Aqidah, 2025)
This study examines the relationship between divine revelation (wahyu) and human intelligence within the framework of Islamic epistemology. Revelation, as an absolute source of divine knowledge, demands the full activation of human potentials including the five senses, intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ) to achieve holistic understanding and avoid reduction to mere linguistic aspects. The primary objective is to bridge modern paradigms and Islamic traditions for the development of integrative education. A qualitative descriptive approach through library research was employed, utilizing thematic-conceptual content analysis of recent literature (2022–2025) and classical Islamic works. Data sources comprised reputable journals, academic books, and databases such as Scopus and Google Scholar, validated through source and theoretical triangulation. The findings reveal that the five senses function as empirical gateways, IQ processes the logical structure of revelatory texts, EQ internalizes moral values, and SQ along with irfani-maʿrifah provides transcendent dimensions. This multidimensional integration prevents partial interpretations of revelation. In conclusion, the results propose a balanced model of Islamic education that produces reflective, empathetic, and spiritually aware individuals as stewards (khalifah) on earth.